The aromaticity of dicupra[10]annulenes. Issue 14 (28th March 2017) - Grande-Aztatzi, Rafael; Mercero, Jose M.; Matito, Eduard; Frenking, Gernot; Ugalde, Jesus M.
Abstract : The aromaticity of dicupra[10]annulenes closely resembles that of naphthalene. Abstract : An extensive theoretical investigation of the electronic structure of a tested fair model dicupra[10]annulene compound, based on the analysis of atom-pair delocalization indices, Bader's molecular graph, the inspection of the canonical molecular orbitals, the z components of their Nuclear Independent Chemical Shifts, NICS(0) zz, and the normalized Giambiagi multicenter delocalization indices, concludes that the perimeter aromaticity of the dicupra[10]annulene ring is consistent with both 10 and 14 π-electron Hückel aromatic 10-membered rings. In either case, the 10-membered ring encloses two 6 π-electron aromatic inner rings, hinged at the Cu–Cu bond. This work demonstrates that the aromaticity of dicupra[10]annulenes closely resembles that of naphthalene. Hence, they are best regarded as metalla-polyacenes, which could make the building blocks of extended structures such as metalated nanotubes.